Renal Tissue Oxygenation Monitoring—An Opportunity to Improve Kidney Outcomes in the Vulnerable Neonatal Population - Harer, Matthew W.; Chock, Valerie Y. (Frontiers in Pediatrics, 2020)
Adequate oxygenation of the kidney is of critical importance in the neonate. Non-invasive monitoring of renal tissue oxygenation using near-infrared spectroscopy (NIRS) is a promising bedside strategy for early detection of circulatory impairment as well as recognition of specific renal injury. As a diagnostic tool, renal NIRS monitoring may allow for earlier interventions to prevent or reduce injury in various clinical scenarios in the neonatal intensive care unit. Multiple studies utilizing NIRS monitoring in preterm and term infants have provided renal tissue oxygenation values at different time points during neonatal hospitalization, and have correlated measures with ultrasound and Doppler flow data. With the establishment of normal values, studies have utilized renal tissue oxygenation monitoring in preterm neonates to predict a hemodynamically significant patent ductus arteriosus, to assess response to potentially nephrotoxic medications, to identify infants with sepsis, and to describe changes after red blood cell transfusions. Other neonatal populations being investigated with renal NIRS monitoring include growth restricted infants, those requiring delivery room resuscitation, infants with congenital heart disease, and neonates undergoing extracorporeal membrane oxygenation. Furthermore, as the recognition of acute kidney injury (AKI) and its associated morbidity and mortality in neonates has increased over the last decade, alternative methods are being investigated to diagnose AKI before changes in serum creatinine or urine output occur. Studies have utilized renal NIRS monitoring to diagnose AKI in specific populations, including neonates with hypoxic ischemic encephalopathy after birth asphyxia and in infants after cardiac bypass surgery. The use of renal tissue oxygenation monitoring to improve renal outcomes has yet to be established, but results of studies published to date suggest that it holds significant promise to function as a real time, early indicator of poor renal perfusion that may help with development of specific treatment protocols to prevent or decrease the severity of AKI.